(untitled) (Progressive Agriculture, 2013)
Bangladesh being a developing country, always tries to control the market prices of coarse rice for stable political and social condition. The main aim of this paper is to find out appropriate deterministic time series model using the latest selection criteria that could best describe the coarse rice price pattern in Bangladesh during the time period July 1975 to December 2011. A total of 438 secondary data on monthly wholesale prices of coarse rice from July 1975 to December 2011 have been used for time series analysis. In this study growth models of different types are fitted using the software package SPSS 20 for the selected time series. The study reveals that cubic model is the best fitted model for wholesale price of coarse rice on the basis of model selection criterion (R2, R2 , RMSE, AIC, BIC, MAE and MAPE). Cubic growth rates varied from 0.68% to 4.03%. After choosing the best growth model by the model selection criteria the coarse rice prices are forecasted for the time period January 2012 to December 2013. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16480 Progress. Agric. 22(1 & 2): 193-201, 2011